Development of Polymer Composites Tubular Housing - Muhammad Hafiz Mohamed Mirrah Mohideen (Nanyang Technological University, 2022)
Development of Polymer Composites Tubular Housing is an important aspect of research for the progression of engineering ventures. Filament winding is an open molding procedure in which the mold is a revolving mandrel. The dominant theory is that filament winding is heavily impacted by winding speed, and temperature variations across the winding system and the mandrel. Previous research involved fabrication of structures with high strength-to-weight ratio. In this study, we would be focusing on the theoretical aspects of these process variables but conducting finite element simulations. The major findings from this study are that the temperature plays a big role in the winding process. The melting point of Polyamide 6, which is the material for the composite used in this study, is 223 Degrees Centigrade. However, due to significant heat loss the heating temperature would need to be increased. It would not be acceptable if the temperature is not ideal, as it would lead to improper composite bonding and higher void content, thus weakening the structural properties of the winded composite. This would mean that further research on the heating parameters should be looked into.